2019
DOI: 10.1002/jcop.22239
|View full text |Cite
|
Sign up to set email alerts
|

Content validation of a quantitative stakeholder engagement measure

Abstract: Aim Using a stakeholder‐engaged approach, this study conducted content validation and item reduction of a quantitative measure of research engagement. Methods A five‐round modified Delphi process was used to reach consensus on items. Rounds 1–3 and 5 were conducted using web‐based surveys. Round 4 consisted of a 2‐day, in‐person meeting. Delphi panelists received individualized reports outlining individual and aggregate group responses after rounds 1–3. Results Over the five‐round process, items were added, dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 35 publications
0
58
0
1
Order By: Relevance
“…more relevant to participants who are engaged in projects that are in or near the dissemination of the collaborative effort. The general acceptability of items suggests that the principles used to guide item selection are acceptable to the community members likely to be encountered or to participate in stakeholder-engaged research and assessment [19], although participants suggested changes in words and terms, as well as item structure. Minimal concerns were related to response options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…more relevant to participants who are engaged in projects that are in or near the dissemination of the collaborative effort. The general acceptability of items suggests that the principles used to guide item selection are acceptable to the community members likely to be encountered or to participate in stakeholder-engaged research and assessment [19], although participants suggested changes in words and terms, as well as item structure. Minimal concerns were related to response options.…”
Section: Discussionmentioning
confidence: 99%
“…A Delphi Process involves administration of multiple rounds of individual online and/or in-person surveys, with participant feedback on aggregated group responses for each round until reaching majority agreement on issues [18]. A five-round, modified Delphi Process was used to reach consensus on engagement principles and items for inclusion, elimination, and revision [19,20]. The number of survey items on each scale (quantity and quality) was reduced from 48 to 32.…”
Section: Item Selectionmentioning
confidence: 99%
“…Although best practices and research for assessing patient group engagement are still evolving, this type of collaboration is recognized as having the potential to significantly improve the clinical trial enterprise [2,18]. Ensuring that collaboration is focused on areas where the greatest benefit can be achieved for everyone involved, given limited resources, is an important step in the development of strong partnerships to improve the relevance of information gathered from clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after Boivin et al’s 2018 systematic review was published, 14 the Patient Engagement In Research Scale (PEIRS) was published as the first tool designed to measure the degree of meaningful patient engagement in research on project teams 16 . The PEIRS is based on an empirical conceptual framework enhanced with a literature review, 5 recognized as a promising and important tool for the evaluation of patient and family caregiver engagement in research 13,17‐20 . The framework outlines the key components of and defines meaningful patient engagement in research as the planned, supported and valued involvement of patients in the research process, which facilitates their contributions and offers a rewarding experience 5 .…”
Section: Introductionmentioning
confidence: 99%